Tsavoenones A–C: unprecedented polyketides with a 1, 7-dioxadispiro[4.0.4.4]tetradecane core from the lichen Parmotrema tsavoense. Issue 32 (3rd August 2018) - Duong, Thuc-Huy; Beniddir, Mehdi A.; Genta-Jouve, Grégory; Aree, Thammarat; Chollet-Krugler, Marylène; Boustie, Joël; Ferron, Solenn; Sauvager, Aurélie; Nguyen, Huu-Hung; Nguyen, Kim-Phi-Phung; Chavasiri, Warinthorn; Le Pogam, Pierre
Abstract : Three racemic polyketides with a novel scaffold are reported from the lichen Parmotrema tsavoense . Abstract : New racemic dispiranic polyketides, tsavoenones A (1 ), B (2 ) and C (3 ), having a novel 1, 7-dioxadispiro[4.0.4.4]tetradecane scaffold were isolated from the foliose lichen Parmotrema tsavoense . These compounds were structurally elucidated by extensive NMR analyses, comparison between experimental and theoretical 13 C NMR data and X-ray crystallography. A putative biosynthetic scenario for the formation of1–3 from parmosidone D, a meta -depsidone previously isolated from the same lichen material, was proposed. Tested for its cytotoxicity, 1 displayed a moderate activity against human myelogenous leukemia K562 cell line with an IC50 value of 66 μg mL −1 .